Seasonality, epidemiology and phylogeny of Theileria ovis with a note on hematological and biochemical changes in asymptomatic infected goats from Pakistan - Irfan, Muhammad; Chang, Shun-Chung; Iqbal, Rana Khalid; Tanveer, Muhammad; Asif, Muhammad; Khan, Adil; Chen, Chien-Chin (Public Library Science, 2023)
Caprine theileriosis, caused by Theileria ovis is a serious production issue, especially in the areas that depend on goats and sheep for milk, meat, and other economic benefits. Pakistan has a large goat population, but few reports have been documented from this country regarding PCR-based detection of T. ovis. The molecular prevalence of T. ovis, on a sea-sonal basis, in various goat breeds enrolled from Muzaffar Garh district of Punjab in Paki-stan was determined from October 2018 to September 2019. In this study, 1084 goat blood samples were screened for the detection of T. ovis DNA through PCR-based amplification of 18S rRNA gene. Out of 1084 goats, 12 (1.11%) were infected with T. ovis. The parasite prevalence varied with the sampling seasons (Chi square test, P = 0.008), and the parasite prevalence was highest in goat blood samples collected in summer (2.39%) followed by win-ter (1.88%). DNA sequencing and BLAST analysis confirmed the presence of T. ovis, and the amplified isolates from the 18S rRNA gene of T. ovis were found to be highly conserved during phylogenetic analysis. Young goats (Fischer exact test, P = 0.022) were found more infected with T. ovis during the winter season. Infected goats had elevated white blood cell counts (Two-sample t-test, P = 0.04), blood urea nitrogen to Creatinine ratio (Two-sample t- test, P = 0.02) and decreased serum Creatinine (Two-sample t-test, P = 0.001) as compared to T. ovis negative goats. We report a relatively low molecular prevalence of T. ovis in goats from the Muzaffar Garh district. However, it is recommended that control measures to eradicate T. ovis infection in goats in this area should be taken.
Keywords: Small Ruminants; Molecular-Detection; Sheep; Amplification; Lestoquardi; Prevalence; Districts